2009
DOI: 10.1007/s11012-009-9277-0
|View full text |Cite
|
Sign up to set email alerts
|

The hydrostatic/hydrodynamic behaviour of an axial piston pump slipper with multiple lands

Abstract: This study considers an analytical approach towards the understanding of the hydrostatic leakage and lift characteristic of a flat slipper of the type used for piston/slipper units within an axial piston pump or motor. In particular it considers a slipper design incorporating a groove on the slipper face and also includes the effect of motion around its associated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…While with positioning the groove near the outer slipper boundary, decreasing the groove width increases the slipper force and consequently decreases the leakage [9]. Later on a CFD is developed and enabled to deal with any number of grooves [10].…”
Section: Swashplate-slipper Pairmentioning
confidence: 99%
“…While with positioning the groove near the outer slipper boundary, decreasing the groove width increases the slipper force and consequently decreases the leakage [9]. Later on a CFD is developed and enabled to deal with any number of grooves [10].…”
Section: Swashplate-slipper Pairmentioning
confidence: 99%
“…The method proposed allows the behavior of the slipper grooves and the second land to be defined without the necessity of having the second land vented. The basis of the theory was outlined in Bergada and Watton (24)- (26) and Watton (27) for flat slipper and in Bergada and Watton (28) for tilted slipper. Consider Fig.…”
Section: Flow and Pressure Distribution On Multiple Land Slippers Mamentioning
confidence: 99%
“…Bargada et al developed a generic analytic method for predicting the leakage rate of the slipper pair, and the results showed that the main source of the leakage in piston pumps is whether the slipper‐swash plate or the barrel‐port plate, producing over 94% of the total leakage. Another work by Bargada et al investigated the leakage and lift characteristic of the grooved slipper. Kumar et al studied the pressure and leakage characteristics of the slipper with a groove by considering the effect of the slipper spinning speed.…”
Section: Introductionmentioning
confidence: 99%